Polymorphisms of the μ‐opioid receptor gene influence cerebral pain processing in fibromyalgia. (2nd November 2020) - Ellerbrock, Isabel; Sandström, Angelica; Tour, Jeanette; Kadetoff, Diana; Schalling, Martin; Jensen, Karin B.; Kosek, Eva
Abstract: Background: Dysregulation of the μ‐opioid receptor has been reported in fibromyalgia (FM) and was linked to pain severity. Here, we investigated the effect of the functional genetic polymorphism of the μ‐opioid receptor gene (OPRM1) ( rs1799971 ) on symptom severity, pain sensitivity and cerebral pain processing in FM subjects and healthy controls (HC). Methods: Symptom severity and pressure pain sensitivity was assessed in FM subjects ( n = 70) and HC ( n = 35). Cerebral pain‐related activation was assessed by functional magnetic resonance imaging during individually calibrated painful pressure stimuli. Results: Fibromyalgia subjects were more pain sensitive but no significant differences in pain sensitivity or pain ratings were observed between OPRM1 genotypes. A significant difference was found in cerebral pain processing, with carriers of at least one G‐allele showing increased activation in posterior cingulate cortex (PCC) extending to precentral gyrus, compared to AA homozygotes. This effect was significant in FM subjects but not in healthy participants, however, between‐group comparisons did not yield significant results. Seed‐based functional connectivity analysis was performed with the seed based on differences in PCC/precentral gyrus activation between OPRM1 genotypes during evoked pain across groups. G‐allele carriers displayed decreased functional connectivity between PCC/precentral gyrus and prefrontal cortex. Conclusions: G‐allele carriers showed increased activation in PCC/precentral gyrus but decreased functional connectivity with the frontal control network during pressure stimulation, suggesting different pain modulatory processes between OPRM1 genotypes involving altered fronto‐parietal network involvement. Furthermore, our results suggest that the overall effects of the OPRM1 G‐allele may be driven by FM subjects. Significance: We show that the functional polymorphism of the μ‐opioid receptor gene OPRM1 was associated with alterations in the fronto‐parietal network as well as with increased activation of posterior cingulum during evoked pain in FM. Thus, the OPRM1 polymorphism affects cerebral processing in brain regions implicated in salience, attention, and the default mode network. This finding is discussed in the light of pain and the opioid system, providing further evidence for a functional role of OPRM1 in cerebral pain processing.